HPV-Driven Head and Neck Cancer: The European Perspective - Wojciech Golusiński; Ewelina Golusińska-Kardach; Piotr Machczyński; Mateusz Szewczyk (Viruses)
Head and neck squamous-cell carcinoma (HNSCC) has long been associated with tobacco and alcohol use. In the last two decades, however, human papillomavirus (HPV) infection has emerged as an important driver of these cancers, particularly in the oropharynx. The eighth edition of the American Joint Committee on Cancer (AJCC) staging system now defines HPV+ and HPV− OPSCC as separate entities. Although our understanding of HPV+ HNSCC continues to improve, it can be challenging to keep up to date with the growing body of evidence. In this context, the present narrative review was carried out to provide an overview of HPV-driven head and neck cancer, with an emphasis on Europe. We review the latest evidence on epidemiology, diagnosis, and treatment, including recent trends towards treatment de-intensification and future directions.